Single-cell sequencing reveals tumor microenvironment features associated with the response to neoadjuvant immunochemotherapy in oral squamous cell carcinoma - Pu-Gen An; Wen-Jie Wu; Xiao Hu; Zi-Qi Zhang; Jie Zhang (Cancer Immunology, Immunotherapy)
Abstract Objectives In recent years, immune checkpoint inhibitors have shown promise as neoadjuvant therapies in the treatment of locally advanced oral squamous cell carcinoma (OSCC). However, the factors affecting the tumor response to immune checkpoint inhibitors (ICIs) remain unclear. This study aimed to analyze the impact of neoadjuvant chemoimmunotherapy (NACI) on the tumor microenvironment of OSCC via single-cell RNA sequencing, with the goal of optimizing treatment strategies. Methods We analyzed biopsy, primary tumor, matched metastatic lymph node, and normal lymph node samples from four patients with OSCC receiving two cycles of tislelizumab (200 mg), albumin-bound paclitaxel (260 mg/m2), and cisplatin (60–75 mg/m2), with 3-week intervals between each cycle. This study explored the tumor microenvironment characteristics of tumors and metastatic lymph nodes in response to NACI. Results We identified two major tumor cell subpopulations (C9 and C11), and patients with high expression of C11 subgroup-specific genes had a lower survival rate. FOXP3+ CD4 eTreg cells were found to potentially suppress the immune response. We found that NACI enhances antitumor immunity by promoting the proliferation of granzyme-expressing CD8+ T effector cells while simultaneously diminishing the effect of CD4+ T cells on Treg-mediated immune suppression. Furthermore, NACI was effective in suppressing inflammatory processes mediated by myeloid cells in tumors, contributing to its antitumor effects. The CCL19+ fibroblastic reticular cell (FRC) subgroup was significantly associated with the efficacy of NACI in patients with OSCC. We found that CCL19+ FRCs primarily exert their antitumor effects through interactions with CD8+ T lymphocytes via the –CXCL12‒CXCR4 axis. Conclusion We explored the immune landscape of primary OSCC tumors and metastatic lymph nodes in relation to clinical response to NACI. Our findings offer valuable insights into patient treatment responses and highlight potential new therapeutic targets for the future management of OSCC.